Behavior of steel reinforced concrete panels subjected to direct tension - Dawood, Nabil Farah A., 1978- (2010)
Thesis (Ph.D.)--Memorial University of Newfoundland, 2010. Engineering and Applied Science Includes bibliographical references (leaves 238-248) Cracking of massive concrete structures like offshore and nuclear power plants structures is an important issue in designing and maintaining such structures. The low tensile strength of concrete can destroy the structural aesthetics and expose steel reinforcements to severe environmental conditions, leading to corrosion of reinforcement and other deterioration. -- The present research investigation ultimately aims to investigate the general behavior of steel-reinforced normal- and high-strength concrete panels subjected to uniaxial and biaxial direct tension loading taking into consideration the effect of the set of parameters that have the most significant effect on the cracking response. This investigation includes experimental, theoretical, and numerical modeling phases for the cracking response. The experimental study incorporates the effect of some important parameters such as the concrete strength, bar diameter, bar spacing, concrete cover, and reinforcement ratio on the cracking response of concrete panels. To conduct the current experimental investigation, a special test setup was designed and fabricated. The loading system was equipped to make it possible to simultaneously apply loads in both directions. Results of the experimental work will be presented in terms of cracking behavior (cracking load, crack spacing, crack width, and crack pattern and the mode of failure), stresses and strains in concrete and steel reinforcement before and after cracking. -- Compared with NSC panels, HSC panels showed lower strains and greater tension stiffening response at a given load level thanks to the corresponding improvement of the bond between the reinforcing steel bars and the high strength concrete matrix. The panels tested under biaxial loading conditions showed lower concrete tensile strength and tension stiffening response, compared with the panels subjected to uniaxial loading conditions. This reduction in the tensile strength of concrete panels subjected to biaxial loading was found to be equal to 5% - 15%. The reduction of the tension stiffening contribution of concrete between cracks due to applying the axial into biaxial direction became more significant as the reinforcing bar diameter was increased. -- An analytical study was conducted to study the bond characteristics between concrete and steel reinforcing bars. Also, a practical and new analytical model, which is capable of predicting the crack spacing of orthogonally reinforced concrete plate panels, was developed. Afterwards, this study developed a model for evaluating crack widths for thick reinforced concrete plates subjected to in-plane axial loading. The calculation procedure was supported by an evaluation of existing test data. -- Finally, the nonlinear analysis of reinforced concrete plates using the damage plasticity model was performed. The tension stiffening model developed in this study was implemented to simulate the cracking response of the concrete. The numerical results show reasonable accuracy in predicting the behavior of steel-reinforced concrete panels.